2012
DOI: 10.1039/c1an15843k
|View full text |Cite
|
Sign up to set email alerts
|

3-Glycidoxypropyltrimethoxysilane mediated in situ synthesis of noble metal nanoparticles: Application to hydrogen peroxide sensing

Abstract: The in situ synthesis is reported of noble metal nanoparticles via 3-glycidoxypropyltrimethoxysilane mediated reduction of 3-aminopropyltrimethoxysilane treated metal salts during sol-gel processing. The method described involves the synthesis of uniform spherical nanoparticles of gold, silver and palladium with controlled size that can be directly utilized for thin film preparation. A detailed study of the synthesis and application of gold nanoparticles to the electrochemical detection of hydrogen peroxide wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 62 publications
1
51
0
Order By: Relevance
“…The properties of as synthesized PdNPs and bimetallic nanoparticles (as shown in Fig. 1) are analogous to that reported earlier [24,26,35,36] justifying novelty of the present process for rapid and controlled synthesis of these nanoparticles under ambient conditions. The time taken during such nanoparticle formation lie between 5 min to 2 h validating the use of 3-APTMS and THF-HPO as most efficient reagents in the synthesis of noble metal nanoparticles and bimetallic nanoparticles.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The properties of as synthesized PdNPs and bimetallic nanoparticles (as shown in Fig. 1) are analogous to that reported earlier [24,26,35,36] justifying novelty of the present process for rapid and controlled synthesis of these nanoparticles under ambient conditions. The time taken during such nanoparticle formation lie between 5 min to 2 h validating the use of 3-APTMS and THF-HPO as most efficient reagents in the synthesis of noble metal nanoparticles and bimetallic nanoparticles.…”
Section: Resultssupporting
confidence: 69%
“…At first instant, the interaction of PdCl 2 and GPTMS need to be reviewed as reported earlier [24]. GPTMS being completely immiscible in water undergo rapid interaction with aqueous solution of palladium chloride.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have studied in details on the role of 3-APTMS and 3-GPTMS during the controlled synthesis of noble metal nanoparticles (AuNPs, AgNPs and PdNPs) [10,11]. It has been found that 3-APTMS capped noble metal salts are converted into their respective nanoparticles in the presence of 3-GPTMS.…”
Section: Role Of 3-aptms and 3-gptms In The Synthesis Of Graphene Andmentioning
confidence: 99%
“…In addition to that some of such functional alkoxysilanes like 3-aminopropyltrimethoxysilane (3-APTMS) and 3-glycidoxypropyltrimethoxysilane (3-GPTMS)) have recently been utilized as reagents and stabilizer during the synthesis of noble metal nanoparticles under ambient [10][11][12]. Further the active role of 3-APTMS has also been demonstrated during the synthesis of prussian blue nanoparticles (PBNPs) [13,14].…”
Section: Introductionmentioning
confidence: 99%